Non-motorized commuting behavior of middle-income working adults in a developing country - Zannat, KE; Islam, KMA; Sunny, DS; Moury, T; Tuli, RD; Dewan, A; Adnan, MSG (American Society of Civil Engineers, 2021)
Although nonmotorized transport (NMT) offers economic, environmental, and health benefits to individuals and communities, understanding nonmotorized travel behavior is a challenging task due to complex interactions of a wide range of factors. While behavioral models offer a conceptual framework to understand human behavior, their use in the study of travel behavior in developing countries is still in its infancy. This study uses three behavioral models—the theory of planned behavior, the theory of triadic influence, and the ecological model of health behavior—to identify potential factors influencing intentions and behavior toward the use of NMT by middle-income working adults, inhabiting the Chittagong City Corporation (CCC) area of Bangladesh. A total of 720 middle-income working adults (aged between 18 and 65 years) were randomly selected and interviewed at major commercial and retail business areas of the CCC. Multiple linear and binary logistic models were developed to quantify the extent of the influence of different factors on nonmotorized mode choice behavior. Results indicated that personal factors (proximal) such as attitude, subjective norm, and behavioral control influence respondents’ intentions and motivation in choosing NMT. However, the current use of NMT was less controlled by intention, while factors associated with the social, cultural, and built environment had (distal) significant influence. The findings of this study could assist urban planners in adopting structural and nonstructural measures to promote NMT use.